2020
DOI: 10.1038/s41598-020-73358-9
|View full text |Cite
|
Sign up to set email alerts
|

Al exposure increases proline levels by different pathways in an Al-sensitive and an Al-tolerant rye genotype

Abstract: Aluminium (Al) toxicity limits crop productivity, particularly at low soil pH. Proline (Pro) plays a role in protecting plants against various abiotic stresses. Using the relatively Al-tolerant cereal rye (Secale cereale L.), we evaluated Pro metabolism in roots and shoots of two genotypes differing in Al tolerance, var. RioDeva (sensitive) and var. Beira (tolerant). Most enzyme activities and metabolites of Pro biosynthesis were analysed. Al induced increases in Pro levels in each genotype, but the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We found higher N content and NR activity in lotus, especially under stress conditions. NR activity, N levels, and N/C ratios were less reduced in the tolerant rye line, which showed an upregulated Orn pathway [ 71 ]. Overall, Pro content strongly increased in barley and lotus, although through different mechanisms, and possibly is directly linked with the N status in plants.…”
Section: Discussionmentioning
confidence: 99%
“…We found higher N content and NR activity in lotus, especially under stress conditions. NR activity, N levels, and N/C ratios were less reduced in the tolerant rye line, which showed an upregulated Orn pathway [ 71 ]. Overall, Pro content strongly increased in barley and lotus, although through different mechanisms, and possibly is directly linked with the N status in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum affects biosynthesis and disturbs the balance of endogenous amino acids in plants [ 3 , 54 , 55 ]. The roots of wheat seedlings responded to Al toxicity by increased exudation of many proteinogenic amino acids [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective action of amino acids against Al toxicity has been repeatedly reported: arginine is involved in the biosynthesis of putrescine, leading to decreased Al retention in the cell walls of wheat [ 57 ]; cysteine increased the activity of glutathione [ 58 ]; GABA induced the antioxidant system in barley [ 59 ] and Arabidopsis thaliana [ 60 ]; glycine played a stress alleviating role as a component of glycine betaine in rice [ 61 ] and glycine-rich proteins in A. thaliana [ 62 ]; phenylalanine was involved in the biosynthesis of phenylpropanoids and flavonoids with defense functions in alfalfa [ 63 , 64 ]; proline protected root cells as an osmolyte [ 55 , 61 , 65 ]; threonine activated H + -ATPase in soybean [ 66 ]. Four of these amino acids (Arg, Cys, GABA, and Gly) were exuded more by the E107 ( brz ) mutant treated with Al ( Figure 8 a–d).…”
Section: Discussionmentioning
confidence: 99%
“…In buckwheat, proline and total sugar content increased proportionally to Al concentration and was implicated in Al tolerance (Pirzadah et al, 2019). In two rye plants with different Al tolerance, de Sousa et al (2020) demonstrated that proline content increased by threefold and 20% in Al-tolerant and Al-sensitive lines respectively due to the regulation of proline biosynthetic pathways which include enhanced glutamate and ornithine pathways for proline biosynthesis and re-oxidation to 1-pyrroline-5-carboxylate. Moreover, Bera et al (2019) revealed that rice plants accumulated high levels of glycine betaine in response to Al exposure.…”
Section: Osmolytes Accumulationmentioning
confidence: 99%